SAJAK “TEMBANG ROHANI” KARYA ZAWAWI IMRON: KAJIAN SEMIOTIK RIFFATERRE - Rina Ratih (Kajian Linguistik dan Sastra, 2013)
The poems composed by Zawawi Imron commonly involve the symbols of nature and Madurase culture such as the sun, moon, clouds, wind, fishing boat, fish, Siwalantrees, bull races and so forth. In the history of modern Indonesian literature, Imron is listed as a prolific poet of the 1960s. This paper explores the meaningful message contained in the poem of Tembang Spiritualwritten by Zawawi Imron. This literature study uses descriptive qualitative research method with semiotic and inter-textual approach. The object of the research is religiosity in the poem of Tembang Spiritual. The qualitative data of this study are in the form of words, phrases, and sentences which are collected by literature review and documentation. Heuristic and hermeneutic or retroactive are applied to analyze the data. The results show that people who keep the promises of their spirit to be obedience to God will receive eternal glorious place on the side of God, as stated in surah Al-a’raf 7, verse 172, surah Al-ma’arij 70, verse 32 and 35, and surah As-sajdah 32, verse 9. Surah Al-a’raf 7, verse 172 is transformed by Imron into the poem of Tembang Spiritual. The relegious elements transformed into the new text have a certain function, i.e. to remind human beings to thank God so that their lives will not suffer.